Value of Sun Protection Factor of Sunscreen Lotion Containing Crude Extract of Photosynthetic Pigments of Porphyridium cruentum as an Active Ingredient in vitro - Perdana Hatta Pafirla, Putra
Crude extract of photosynthetic pigments of Porphyridium cruentum are potential to be apply as a sunscreen. This research aimed to determine the value of sun protection factor (SPF) of sunscreen lotion containing crude extract of photosynthetic pigments of P. cruentum. The research method included cultivation of P. cruentum, photosynthetic pigments extraction with acetone, characterization of the crude extract of photosynthetic pigments by thin layer chromatography (TLC), photosynthetic pigments purification by silica column chromatography, pure pigment characterization by UV-Vis spectrophotometry, preparation sunscreen lotion containing crude extract of photosynthetic pigments of P. cruentum, and determination of SPF value of the sunscreen lotion using Mansur method. The result showed that P. cruentum cells cultured in a total volume of 18.9 L for 10 day ware 17.8005 ± 0.7051 g dry biomass. Crude extract of photosynthetic pigments of P. cuentum obtained from the extraction of 10 g dry biomass were 2.04 ± 0.01 g, or equivalent to a yield of 24%. The SPF value of sunscreen lotion containing crude extract of photosynthetic pigments of P. cruentum with concentrations of 0.25, 1.0, and 2.5% (w/w) was 0.30, 1.16, and 1.78, respectively.